EFEKTIFITAS INTERVENSI PENDEKATAN COGNITIVE BEHAVIOUR THERAPY UNTUK MENINGKATKAN ACADEMIC SELF EFFICACY PADA MAHASISWA DENGAN PRESTASI AKADEMIK YANG RENDAH - Yenny Astria (MANASA, 2013)
The objective of this research is to know effectiveness of intervention with the approach of cognitive behaviour therapy (CBT) are made in the form of brief to increase academic self efficacy on college student with low academic self efficacy. The two partisipans are undergraduate students who is actively enrolled 4th semesters, has GPA under 2,25, and having low academic self efficacy based on College Academic Self Efficacy (CASES) score. Result of this research showed that intervention with the approach of cognitive behaviour therapy (CBT) that are made in the form of brief effective to increase academic self efficacy college student with low academic self efficacy. Both of participants show improvement CASES score on post test. Interview result also shows that participants feel positive benefit after following this intervention.